Experimental investigation of motion responses of tunnel element immerging by moored barge - 左卫广 王永学 (Journal of hydrodynamics. Series B, 2015)
In this paper, the barge effect on the motion responses of the tunnel element immerging by the moored barge under waves is investigated experimentally. Both the motion responses of the tunnel element and the moored barge in the experiment are simultaneously acquired by the Untouched 6-D Measurement System. The results show that the sway motion responses of the tunnel element immerging by the moored barge are different from those without the barge. For the system of the tunnel element and the moored barge, the moored barge has two motion components in the sway direction. The high frequency motion of the moored barge has little effect on the high frequency motion of the tunnel element with moored barge. However, the low frequency motion of the moored barge has a significant effect on the sway motion of the tunnel element. The motion responses of the tunnel element and the barge in the heave and roll directions are mainly the high frequency motion.